A COMPARATIVE ANALYSIS OF PRE-SERVICE AND IN-SERVICE TEACHERS’ INTERNET SAFETY LEVEL, CYBERBULLYING ENCOUNTERED EXPERIENCES, AND CYBERBULLYING PERCEPTIONS; THAILAND PERSPECTIVE - Tantaphalin, Piyapot; Suwannatthachote, Praweenya; Punlumjeak, Kiatisak (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2017)
Abstract The focus of this study was to compare the difference ofpre-service and in-service teachers’ internet safety level, cyberbullying encountered experiences, and cyberbullying perceptions in terms of various variables. The survey collected from 102 pre-service teachers and 133 in-service teachers in Thailand by online questionnaires. The result showed pre-service and in-service teachers’ internet safety level, cyberbullying encountered experiences,andcyberbullying perceptions didn’t have any differences in term of gender, age,internet usage time and teaching experience.Only in-service teachers had significant different internet safety level in terms of ICT-related field of teaching. Moreover, they had significant different cyberbullying encountered experiences in terms of internet safety too. In addition, both of pre-service and in-service teachers had significant different cyberbullying perceptions in term of internet safety level and cyberbullying encountered experiences. Compared between pre-service and in-service teachers’ internet safety level, cyberbullying encountered experiences, and cyberbullying perceptions, they show no significant difference. The majority of pre-service and in-service teachers thoughtthey can deal with cyberbullying in school but they want some development. Furthermore, they thoughtcyberbullying topic should be extra-curricular activities in teacher’s curriculum. Keyword : Internet safety, Cyberbullying, Pre-service teacher, In-service teacher